2017
DOI: 10.18203/2394-6040.ijcmph20174815
|View full text |Cite
|
Sign up to set email alerts
|

Crimean-Congo haemorrhagic fever: knowledge and practices of doctors at a tertiary care hospital in Lahore

Abstract: Background: Crimean-Congo haemorrhagic fever (CCHF) is a potentially fatal yet preventable zoonotic haemorrhagic disease which has consumed the lives of many health care workers in different regions of Pakistan over the past few years. There is neither a specific therapy nor an effective vaccine for the disease, which makes prevention the most rational approach towards CCHF. Hence, our main objective in this study was to determine the knowledge and practices of doctors regarding Crimean-Congo haemorrhagic feve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…To the best of our knowledge, this was the first nationwide study to investigate the knowledge, attitudes, and practice among general people residing in Pakistan. Previous studies in Pakistan had a small number of participants or were restricted to healthcare workers [28][29][30]. Our study revealed that Pakistani people had poor levels of knowledge, attitudes, and practices towards the CCHF.…”
Section: Discussionmentioning
confidence: 70%
“…To the best of our knowledge, this was the first nationwide study to investigate the knowledge, attitudes, and practice among general people residing in Pakistan. Previous studies in Pakistan had a small number of participants or were restricted to healthcare workers [28][29][30]. Our study revealed that Pakistani people had poor levels of knowledge, attitudes, and practices towards the CCHF.…”
Section: Discussionmentioning
confidence: 70%